STUDI PEMAHAMAN DAN PERSEPSI REMAJA TENTANG SEKSUALITAS DI ERA DIGITAL DI DESA TABEAK BLAU KECAMATAN LEBONG ATAS KABUPATEN LEBONG PROVINSI BENGKULU - Resi Erla Nova. RE; Safitra, Linda (JURNAL ILMIAH IDEA, 2024)
This study aims to understand the understanding and perception of rural adolescents about sexuality in the digital era, with a case study in Tabeak Belau Village, Lebong Atas District, Lebong Regency, Bengkulu Province. Using qualitative methods and a case study approach, this study involved 13 informants consisting of the village head, six adolescents who married early, and six of their parents. Data were collected through observation, interviews, and documentation, then analyzed through data reduction, data presentation, and drawing conclusions. The analysis is based on Mead's Symbolic Interactionism Theory. The results showed that adolescents understand sexuality as something common and easily accessible via the internet. Based on Mead's Symbolic Interactionism Theory, the meaning of sexuality for adolescents is formed through social interactions with peers, social media, and personal experiences. Although they are aware of the risks of premarital sexual relations, the symbols and meanings constructed in their social environment make sexuality seen as something normal. Adolescents' perceptions are influenced by the symbol of dating as a form of commitment, where sexual relations are considered an expression of affection and emotional closeness. The process of forming adolescents' self-identity is also influenced by how they interpret sexuality in their social context, including social pressure and expectations from peer groups. This study reveals how technology and social interactions shape adolescents' understanding and behavior regarding sexuality in the digital era, in line with the principles of Symbolic Interactionism Theory which emphasizes that meaning emerges from social processes and relationships between individuals.